2010
DOI: 10.1111/j.1469-8986.2010.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural generators of sensory gating in schizophrenia

Abstract: Although malfunctioning of inhibitory processes is proposed as a pathophysiological mechanism in schizophrenia and has been studied extensively with the P50 gating paradigm, the brain regions involved in generating and suppressing the P50 remain unclear. The current investigation used EEG source analysis and the standard S1-S2 paradigm to clarify the neural structures associated with P50 gating in16 schizophrenia patients and 14 healthy subjects. Based on prior research, the superior temporal gyrus, hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 78 publications
(92 reference statements)
2
46
0
Order By: Relevance
“…The frontocortical sources during the processing of auditory stimuli have been implicated in the MEG studies of nonpatients (Mayer et al, 2009;Weisser et al, 2001) and intracranial recordings in epileptic patients (Grunwald et al, 2003;Korzyukov et al, 2007). Moreover, Williams et al (2011) reported EEG evidence of an association between enhanced gating-related dipole activity in the dorsolateral prefrontal cortex and higher gating ratios in schizophrenia subjects, which might point to a relationship between working memory and sensory gating.…”
Section: Discussionmentioning
confidence: 95%
“…The frontocortical sources during the processing of auditory stimuli have been implicated in the MEG studies of nonpatients (Mayer et al, 2009;Weisser et al, 2001) and intracranial recordings in epileptic patients (Grunwald et al, 2003;Korzyukov et al, 2007). Moreover, Williams et al (2011) reported EEG evidence of an association between enhanced gating-related dipole activity in the dorsolateral prefrontal cortex and higher gating ratios in schizophrenia subjects, which might point to a relationship between working memory and sensory gating.…”
Section: Discussionmentioning
confidence: 95%
“…Source localization studies implicate a neural network involving prefrontal cortex, particularly the dorsolateral prefrontal cortex (dlPFC), superior temporal gyrus (STG), hippocampus, and thalamus in the generation of P50 and its suppression (25, 26). Notably, dlPFC and hippocampus have been associated with working memory dysfunction in schizophrenia (27, 28), while prefrontal cortex, hippocampus, and STG structural and functional abnormalities have been implicated in efficient information processing (29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…The observed over-activity, which has now been replicated using a more ecologically valid stimulus (Tregellas et al, 2009), was interpreted as consistent with the concept of impaired inhibitory function in schizophrenia (Lewis and Moghaddam, 2006). A recent high-density EEG study by Williams and colleagues (2011) also suggested involvement of these regions in P50 sensory gating, and abnormal function of the hippocampus and prefrontal cortex in patients (Williams et al, 2011). …”
Section: Introductionmentioning
confidence: 99%